2017
DOI: 10.1002/hep.28951
|View full text |Cite
|
Sign up to set email alerts
|

IL6‐mediated inflammatory loop reprograms normal to epithelial‐mesenchymal transition+ metastatic cancer stem cells in preneoplastic liver of transforming growth factor beta–deficient β2‐spectrin+/− mice

Abstract: Hepatocellular carcinoma (HCC) is the second-leading cause of cancer-related deaths world-wide with poor survival rate. As many as 40% of HCCs are clonal, with alteration of key tumor suppressor pathways in stem cells is the primary cause of HCC initiation. However, mechanisms that generate metastatic stem cells in pre-neoplastic liver tissue are not well understood. We hypothesized that chronic inflammation is a major driver of the transformation of genetically defective liver stem cells (LSCs) into highly me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 48 publications
2
59
0
Order By: Relevance
“…PJA1/wt/LSCs and PJA1/Smad3 þ/À /LSCs were isolated from single mice and immediately seeded and cultured onto 96well plates (3 Â 10 3 cells/well) in suitable supplement-containing medium. Cell proliferation was measured using CyQUANT NF Cell Proliferation Assay reagent at day 1, 3, and 6 as described previously (32). Data are from three independent experiments.…”
Section: Cell Proliferation and Viability Assaymentioning
confidence: 99%
“…PJA1/wt/LSCs and PJA1/Smad3 þ/À /LSCs were isolated from single mice and immediately seeded and cultured onto 96well plates (3 Â 10 3 cells/well) in suitable supplement-containing medium. Cell proliferation was measured using CyQUANT NF Cell Proliferation Assay reagent at day 1, 3, and 6 as described previously (32). Data are from three independent experiments.…”
Section: Cell Proliferation and Viability Assaymentioning
confidence: 99%
“…which is an important part of tumor progression and metastasis [28]. EMT-related markers such as E-cadherin and EMT transcription factors such as Twist, snail, and slug are important indicators of alterations to the EMT.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…Increased IL-6 expression has been reported to drive CSCs expansion through STAT3 activation in HCC [118] . Moreover, a recent study has demonstrated that EMT+ metastatic CSCs can be generated in a β2SP +/mouse model of HCC, mainly due to overexpression of IL-6 in addition to the partial disruption of TGF-β signaling [119] .…”
Section: Janus Kinase/signal Transducers and Activators Of Transcriptmentioning
confidence: 99%